Identification of a novel ephemerovirus in a water buffalo (Bubalus bubalis [Linnaeus, 1758]) - IMAI, Sakiho; KISHIMOTO, Mai; HORIE, Masayuki (Journal of Veterinary Medical Science, 2024)
Ephemeroviruses, belonging to the genus Ephemerovirus within the family Rhabdoviridae of the Mononegavirales, are non-segmented, negative-strand RNA viruses that infect artiodactyls and blood-sucking arthropods. Although recent advances in sequencing technology have facilitated the identification of novel ephemeroviruses, thereby expanding our understanding of this viral genus, their diversity remains elusive, as evidenced by phylogenetic gaps between currently known ephemeroviruses. In this study, we analyzed publicly available RNA-seq data and identified a novel ephemerovirus, tentatively named Punjab virus (PBV), in a water buffalo (Bubalus bubalis [Linnaeus, 1758]). We obtained two separate PBV contigs from the RNA-seq data; the first contig covers the N, P, and M genes, while the second contig covers the G, α, β, γ, and L genes. Together, these PBV contigs represent 99% of the estimated complete viral genome. Mapping analysis revealed a typical transcriptional gradient pattern commonly observed in mononegaviruses, suggesting that the water buffalo is the authentic host for PBV. Sequence comparisons with its closest relatives indicate that the newly identified virus meets the ICTV species demarcation criteria for sequence divergence. Thus, this study contributes to a deeper understanding of the diversity of ephemeroviruses.